1978
DOI: 10.1037/0022-0167.25.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social modeling, cognitive structuring, and self-management strategies on affective self-disclosure.

Abstract: The purpose of these companion studies was to assess immediate and delayed effects of social modeling, cognitive structuring, and two self-management strategies for increasing affective self-disclosure in undergraduate males. Subjects were randomly assigned to (a) social modeling, (b) cognitive structuring, (c) attention placebo, or (d) no-training control groups. Following training, subjects took a performance test and two pencil-and-paper measures. With this treatment used as a blocking variable, subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Although social learning theory has been used to investigate a broad array of communicative behaviors, including language acquisition (Chernela, 2004), learning and developing communication skills (Whitehurst, 1976;Whitehurst & Merkur, 1977;Whitehurst, Sonnenschein, & Ianfolla, 1981), and self-disclosure (Highlen & Voight, 1978), researchers investigating social modeling processes in the family have focused primarily on the intergenerational transmission of family violence (e.g., Gelles, 1994;Stamp, 2004), the development of social skills in children (e.g., Burleson & Kunkel, 2002;Gardner & Cutrona, 2004), and the creation and perpetuation of age and gender stereotypes (Kunkel et al, 2006) . For example, Gelles (1994) found that abuse may be socially learned in the family through both being abused and observing the act or process of abuse.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Although social learning theory has been used to investigate a broad array of communicative behaviors, including language acquisition (Chernela, 2004), learning and developing communication skills (Whitehurst, 1976;Whitehurst & Merkur, 1977;Whitehurst, Sonnenschein, & Ianfolla, 1981), and self-disclosure (Highlen & Voight, 1978), researchers investigating social modeling processes in the family have focused primarily on the intergenerational transmission of family violence (e.g., Gelles, 1994;Stamp, 2004), the development of social skills in children (e.g., Burleson & Kunkel, 2002;Gardner & Cutrona, 2004), and the creation and perpetuation of age and gender stereotypes (Kunkel et al, 2006) . For example, Gelles (1994) found that abuse may be socially learned in the family through both being abused and observing the act or process of abuse.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…References to emotive states have not been previously studied in naturally occurring English-language conversations, but they have been examined in role-playing studies. In three such studies designed to elicit emotional responses to an equal number of hypothetical positive (pleasant) and negative (unpleasant) situations, participants talked more about pleasant emotions than unpleasant ones (9,10,11). Respondents also reported experiencing more anxiety when talking about unpleasant emotions than pleasant ones.…”
mentioning
confidence: 99%
“…Recently, Dell (1982a) questioned the epistemological correctness of the resistance concept. Dell noted that resistance Although there is evidence that language and perception is used as an-explanatory device to account for a situation in can be changed through a focus on changing overt behavior (Highlen & Voight, 1978;Lefcourt, Hogg, Struthers, & Holmes, which the client does not respondto therapeutic interventions 1975), we have found that this is usually not the most proin the manner predicted by the therapist. Resistance is an attribution made by the therapist to account for "difficulties" ductive route for intervention efforts.…”
Section: H Russell Searight Patrick Openlandermentioning
confidence: 61%